Pain management of chronic wounds: Diabetic ulcers and beyond. (November 2018) - Paschou, Stavroula A.; Stamou, Maria; Vuagnat, Hubert; Tentolouris, Nicholas; Jude, Edward
Highlights: Patients who suffer from ulcers very often experience pain. Early identification and prompt treatment are key to pain management. Further management should focus on the appropriate dressing. Systematic pain medication is sometimes needed. Abstract: Patients who suffer from ulcers often experience pain of sufficient severity to reduce their quality of life. The aim of this review article is to collect, analyze and qualitatively resynthesize information regarding the definition and prevalence of ulcer pain, the pathophysiology of such pain, its assessment, and the optimal systemic and topical treatments. Early identification and prompt treatment are key to pain management. Further management should focus on appropriate dressing as much as on pain medication. The goal is to provide maximum relief with minimum side-effects.